Inotropic myocardial reserve deficiency is the predominant feature of exercise haemodynamics in cardiac amyloidosis. (24th August 2017) - Clemmensen, Tor Skibsted; Mølgaard, Henning; Sörensen, Jens; Eiskjaer, Hans; Andersen, Niels Frost; Mellemkjaer, Søren; Andersen, Mads Jønsson; Tolbod, Lars Poulsen; Harms, Hendrik J.; Poulsen, Steen Hvitfeldt
Abstract: Aims: This study aimed to characterize invasive haemodynamics during exercise in subjects with cardiac amyloidosis (CA). Methods and results: The study population numbered 44 subjects. Group A (CA‐positive, n  = 24) comprised wild‐type transthyretin patients ( n  = 10), familial transthyretin amyloidosis mutation carriers (ATTRm) with cardiac involvement ( n  = 5), and light‐chain amyloidosis patients with cardiac involvement ( n  = 9). Group B (CA‐negative, n  = 20) comprised four healthy ATTRm subjects without cardiac involvement documented by 11 C‐PIB positron emission tomography and 16 healthy controls. All subjects underwent a symptom‐limited, semi‐supine exercise test with expired gas analysis and simultaneous right heart catheterization. CA patients had lower peak oxygen consumption [15 ± 6 mL/min/kg bodyweight (bwt) vs. 33 ± 7 mL/min/kg bwt; P  < 0.0001] than controls. Myocardial reserve during exercise was significantly reduced in CA patients as reflected in a small increase in stroke volume index (SVI) and cardiac index (CI) compared with controls [ΔSVI: 4 mL/m 2 (range: −1 to 8) vs. 14 mL/m 2 (range: 5–25); P  < 0.0001; ΔCI: 2 ± 2 L/min vs. 7 ± 2 L/min; P  < 0.0001]. During exercise, CA patients had significantly higher left and right ventricular filling pressures than controls. Furthermore, CA patients had severely impaired pulmonary arterial compliance (PAC) compared with controls [2.9 mL/mmHg (range: 2.1–4.5) vs. 7.5 mL/mmHg (range: 5.7–10.4); P  < 0.0001]. Conclusions: Cardiac amyloid deposits are associated with severely reduced inotropic myocardial reserve and increased left and right ventricular filling pressures during exercise. Furthermore, CA subjects have severely reduced PAC, which may contribute to right heart failure and reduced exercise capacity.